Exploring environmental identity at work and at home: A multifaceted perspective - Charlotte Blanchard; Maxime Paquet (Current Research in Ecological and Social Psychology, 2023)
Research on pro-environmental behaviors at work (PEBWs) has focused on several individual level antecedents, such as attitudes and knowledge about climatic issues, over the past two decades. Environmental identity, another individual factor, is a promising PEBW predictor, but it has not been studied much in the context of work and fails to be defined in an exhaustive and consistent manner. This research aims to develop a better understanding of the environmental identity concept and to describe how environmental identity can vary in different contexts, namely the work and personal spheres.For this research, 12 workers of diverse fields were invited to partake in a 30 min interview in order to validate the dimensions of environmental identity stemming from scientific literature, and to identify new themes from the interviewees’ discourse.The results of the content analysis show that environmental identity is multilayered, having individual (ex: environmental consciousness, desire to connect with nature) and social (ex: group membership, social representations) components. Moreover, context is important in understanding this identity facet, as it can be more salient at work or at home.This study helps conceptualize environmental identity in a way that will eventually facilitate its quantitative measurement. This will benefit studies on the impact of environmental identity on PEBWs, therefore guiding how organizations and leaders might encourage them in alignment with workers’ environmental identity.